Lower Blood Pressure Is Not Associated With Decreased Arterial Spin Labeling Estimates of Perfusion in Intracerebral Hemorrhage. Issue 11 (4th June 2019) - Klahr, Ana C.; Kosior, Jayme C.; Dowlatshahi, Dariush; Buck, Brian H.; Beaulieu, Christian; Gioia, Laura C.; Kalashyan, Hayrapet; Wilman, Alan H.; Jeerakathil, Thomas; Emery, Derek J.; Shuaib, Ashfaq; Butcher, Kenneth S.
Abstract : Background: Subacute ischemic lesions in intracerebral hemorrhage (ICH) have been hypothesized to result from hypoperfusion. Although studies of cerebral blood flow (CBF) indicate modest hypoperfusion in ICH, these investigations have been limited to early time points. Arterial spin labeling (ASL), a magnetic resonance imaging technique, can be used to measure CBF without a contrast agent. We assessed CBF in patients with ICH using ASL and tested the hypothesis that CBF is related to systolic blood pressure (SBP). Methods and Results: In this cross‐sectional study, patients with ICH were assessed with ASL at 48 hours, 7 days, and/or 30 days after onset. Relative CBF (rCBF; ratio of ipsilateral/contralateral perfusion) was measured in the perihematomal regions, hemispheres, border zones, and the perilesional area in patients with diffusion‐weighted imaging hyperintensities. Twenty‐patients (65% men; mean±SD age, 68.5±12.7 years) underwent imaging with ASL at 48 hours (N=12), day 7 (N=6), and day 30 (N=11). Median (interquartile range) hematoma volume was 13.1 (6.3–19.3) mL. Mean±SD baseline SBP was 185.4±25.5 mm Hg. Mean perihematomal rCBF was 0.9±0.2 at 48 hours at all time points. Baseline SBP and other SBP measurements were not associated with a decrease in rCBF in any of the regions of interest ( P ≥0.111). rCBF did not differ among time points in any of the regions of interest ( P ≥0.097). Mean perilesional rCBF was 1.04±0.65 and was unrelated to baseline SBP ( P =0.105). Conclusions: ASL can be used to measure rCBF in patients with acute and subacute ICH. Perihematomal CBF was not associated with SBP changes at any time point. Clinical Trial Registration: URL: http://www.clinicaltrials.gov . Unique identifier: NCT00963976.